Taiwanese Dermatological Association consensus for the management of atopic dermatitis - Chia-Yu Chu; Chi-Hung Lee; I-Hsin Shih; Hsiu-Chin Chen; Po-Han Huang; Chin-Yi Yang; Wen-Jen Wang; Yi-Ju Chen; Hamm-Ming Sheu; Wei-Ming Wang; Woan-Ruoh Lee; Yuan-Hsin Lo; et al. (Wolters Kluwer Medknow Publications, 2015)
Background/Objective: This report describes the 2014 consensus of the Taiwanese Dermatological Association (TDA) regarding the treatment of atopic dermatitis (AD). The TDA consensus is distributed to practices throughout Taiwan to provide recommendations for therapeutic approaches for AD patients to improve their quality of life. Methods: The information in the consensus was agreed upon by a panel of national experts at TDA AD consensus meetings held on March 16, May 4, and June 29, 2014. The consensus was in part based on the 2013 Asia-Pacific AD guidelines and the guidelines of the American Academy of Dermatology, with modification to reflect the clinical practice in Taiwan. Results: The amendments were drafted after scientific discussions focused on the quality of evidence, risk, and benefits; all the consensus contents were voted on by the participating dermatologists, with approval by at least 75% for inclusion. Conclusion: The consensus provides a comprehensive overview of treatment for AD, with some local and cultural considerations for practitioners in Taiwan, especially the use of wet dressings/wraps, systemic immunomodulatory agents, and complementary therapies.